The Relationship between Learning Styles (Kolb Learning Styles) and Adaptive Teaching Method; A Case Study on Students of JahadeDaneshgahiApplied Scientific University of Zahedan Iran the Second Semester of 20142015 Educational Year - Mahbubeh Kahkhayi; Naser Nastiezaie (Kerman University of Medical Sciences, 2016)
Background & Objective: Knowledge about the nature and types of learners learning styles can help teachers to adjust their teaching methods with students learning styles to achieve the desired educational outcomes This study aimed to investigate the relationship of students learning styles (based on Kolb learning Styles) and adaptive teaching method Methods: In this descriptivecorrelation study 250 students in ElmiKarbordi higher education ‎center at Zahedan JahadeDaneshgahi Iran were selected via simple random sampling model For collecting the data the learning styles of Kolb and adaptive teaching method questionnaires were used The data were analyzed using Pearson correlation and regression analysis tests Results: The amounts of correlation coefficient of assimilating divergent accommodating convergent learning styles and adaptive teaching method were 0810 0765 0795 and 0809 respectively (P < 0001) In addition based on the regression analysis of learning styles convergent (β = 0491) and divergent (β = 0300) methods had the greatest impacts on adaptive teaching method respectively (P < 0001) Conclusion: Given the positive and meaningful correlation between the learning styles with adaptive teaching method teachers of educational centers are suggested to use adaptive teaching method based on learningbased activities assessment of learners needs engaging students in the teaching process and flexibility for personal development